The Ummi Method for Enhancing Quranic Reading Skills: A Study among Housewives - Alghozi, Alan Alifudin; Husna, Difa'ul (Institut Darul Falah Bandung Barat, 2025)
Low Qur'anic literacy among homemakers remains a critical challenge, despite their vital role as the first educators within the family. This study aimed to analyze the implementation of the Ummi method as an alternative model to enhance Qur'anic reading skills among homemakers in Kralas Village, Bantul, Yogyakarta. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. Eight informants, including two teachers and six participants, were selected using the snowball sampling technique. The findings revealed that learning was carried out through a systematic process, spanning from planning to closure. The novelty of this study lies in the application of two-way evaluation, where both teachers and participants assessed each other, and in identifying the importance of teacher certification and participatory learning management for adult learners. Academically, this research enriches the literature on Qur’anic education based on andragogy, while practically, it offers a replicable community-based model to empower homemakers in strengthening family Qur'anic literacy.